SPOR BİLİMLERİ ÖĞRENCİLERİNİN BEDEN EĞİTİMİ VE SPOR ÖĞRETMENLİĞİNE YÖNELİK TUTUMLARI. - DENİZ, Sabahattin; GÖRGEN, İzzet (Electronic Turkish Studies)
The current study aims to investigate the attitudes of sports sciences faculty students towards becoming a physical education and sports teacher. The study group of the current research employing the survey model is comprised of students having graduated from the faculty of sports sciences and the senior students of the faculty of sports sciences enrolled in the pedagogical formation program given in the Education Faculty of Muğla Sıtkı Koçman University in the spring term of 2017- 2018 academic year. A total of 126 pre-service teachers participated in the study on a volunteer basis. Of the participating students, 45 (35.7%) are females and 81 (64.3%) are males. In order to determine the betweengroups differences, t-test and "variance analysis" were used. The findings of the current research have revealed that the students' love for and anxiety about the profession do not vary significantly depending on gender, department (sports management, coaching, recreation and physical education and sports teaching) and whether their mothers and father do sports. It was also found that the love for the profession of teaching of the pre-service sports sciences teachers who had teaching experience before is higher than those who did not. Moreover, the pre-service sports science teachers whose love for the profession of teaching is higher stated that if they were given a chance to select their branch today, they would more likely select sports sciences when compared to those whose love for the profession is relatively lower. Though the students' parents' interest in sports is low, their willingness and motivation to engage in the field of sports is high. These students accepted to their departments through special talent exams can only be appointed as physical education and sports teachers if they receive pedagogical formation training. A low and positive correlation was found between the students' love for the profession and anxiety about it.